Designing and Evaluating a Platform for Robot-Assisted Minimally Supervised Hand Therapy: A Pilot Study - Reddy Kalli, Venkata Dinesh (Journal of Artificial Intelligence General science (JAIGS) ISSN:3006-4023, 2024)
Background Robot-assisted therapy has the potential to enhance therapy doses post-stroke, addressing the often insufficient treatment of hand function in clinical settings and after discharge. Traditionally, these systems have been complex and required therapist supervision. To better leverage robot-assisted therapy, we propose a platform designed for minimal therapist supervision and present a preliminary evaluation of its immediate usability, addressing a key challenge often neglected in real-world applications. This approach could increase therapy doses by enabling a single therapist to train multiple patients simultaneously, as well as supporting independent training in clinics or at home. Methods We implemented design changes on a hand rehabilitation robot, focusing on enabling minimally-supervised therapy. This involved developing new physical and graphical user interfaces and creating two functional therapy exercises aimed at training hand motor coordination, somatosensation, and memory. Ten participants with chronic stroke evaluated the platform's usability and reported their perceived workload during a minimally-supervised therapy session. The ability to use the platform independently was assessed using a checklist. Results After a brief familiarization period, participants were able to independently perform the therapy session, needing assistance in only 13.46% (range: 7.69–19.23%) of the tasks. They rated the user interface and exercises highly on the System Usability Scale, with scores of 85.00 (75.63–86.88) and 73.75 (63.13–83.75) out of 100, respectively. Nine participants indicated they would use the platform frequently. The perceived workload was within acceptable ranges. The most challenging tasks identified were object grasping with simultaneous control of forearm pronosupination and stiffness discrimination. Discussion Our findings indicate that a robot-assisted therapy device can be safely and intuitively used with minimal supervision upon first exposure by adhering to usability and workload requirements. The preliminary usability evaluation highlighted specific challenges that need to be addressed to enable real-world minimally-supervised use. This platform could complement conventional therapy, providing increased therapy doses with existing resources and establishing a continuum of care that transitions from the clinic to the home.